ANALYSIS OF LEGAL CERTAINTY OF HALAL PRODUCT ASSURANCE SYSTEM POST OMNIBUS LAW - Ibnu Anwarudin; Abdullah Sulaiman (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
To be able to answer how the construction of the implementation of the halal product guarantee system should be (das sollen) as the aim of regulating halal certification which adheres to the mandatory principle and is in line with the rule of law which prioritizes the principles of justice, benefit and legal order, it is necessary to harmonize the Law on Halal Product Assurance and the regulations implementation and maintain the consistency of the application of norms. In this paper, the author will present an ideal construction idea so that legal certainty in the implementation of halal product guarantees can be realized as the goal of the Halal Product Guarantee Law by applying Aristotle's rule of law theory (grand theory), which is supported by the theory of authority and the theory of responsibility (middle range). theory) and the theory of legal certainty (applied theory). From the application of the theoretical study, several weaknesses were identified in the substance of the norms of sanctions in the Halal Product Guarantee Law which have the potential to hinder legal certainty for halal product guarantees. Setting norms for sanctions against business actors who violate the provisions of Article 4 of the Law on Halal Product Guarantee must be stated explicitly in the provisions of the Law on Halal Product Guarantee. Drugs, biological products, and medical devices that do not comply with halal requirements and are subject to stages of halal certification obligations until October 17, 2039 can still be circulated with the obligation to include non-halal information, so that the public gets clear information on the halalness of a product by emphasizing product responsibility. business actors (product liability). In the field of supervision,